Analytical model for saturation drain current and substrate current of fully overlapped LDD MOSFET - Kumar,, A; Gupta, , RS; Haldar,, S; Bindra, , S; Singh,, A; Bose,, S; Kalra,, E (2001)
An analytic model for saturation drain current and substrate current of fully overlapped lightly doped drain (FOLD) MOSFET is developed using pseudo-two-dimensional approximation in the channel and drain regions and expression of maximum electric field is obtained. An expression for channel length modulation factor is also developed and the substrate current is calculated.